Multicenter evaluation of fast multiplex PCR for detection of pathogens in lower respiratory tract infections - Wang, Ling; Cai, Jingyao; Dai, Lizhong; Miao, Weimin; Li, Ziyang; Cao, Wei; Huang, Sisong; Sun, Mei; Xia, Lehuan; Jiang, Xixin; Wang, Pingbang; Pan, Jianhua; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThis study aimed to compare the diagnostic performance between bacterial culture and a rapid multiplex PCR assay (Respiratory Pathogens Multiplex Nucleic Acid Diagnostic Kit) for detecting six bacterial (Pseudomonas aeruginosa, Klebsiella pneumoniae, Staphylococcus aureus, Streptococcus pneumoniae, Haemophilus influenzae, Legionella pneumophila) and six viral targets (Influenza A/B, Respiratory syncytial virus, Adenoviruses, Human rhinovirus, Mycoplasma pneumoniae) in 728 bronchoalveolar lavage (BAL) specimens.MethodsThis multicentric observational study was conducted at six comprehensive large hospitals in Hunan Province, China (May to October 2023) and assessed performance of mPCR kit by comparison with conventional culture method.ResultsThe mPCR kit detected ≥1 pathogen in 628 specimens (positivity rate: 86.3%), demonstrating positive percentage agreement (PPA) of 84.6% (95% CI: 76.6-92.6%) and negative percentage agreement (NPA) of 96.5% (95% CI: 96.0-97.1%) versus culture. Notably, semi-quantitative concordance was 79.3% (283/357) for culture-positive specimens. Multiple pathogens were detected by mPCR in 144 samples (19.8%). Lower Ct values (≤30) correlated strongly with culture positivity.ConclusionsThe mPCR kit is a simple and rapid molecular test that could complement conventional culture method for improvement of diagnosis accuracy of Lower respiratory tract infections.